Intrapartum PCR-assay for detection of Group B Streptococci (GBS) - Rikke B Helmig; Jan B Gertsen (Elsevier, 2019)
Objective: We have recently introduced intrapartum PCR-testing for group B streptococcus (GBS) in women in labor with prolonged rupture of membranes or preterm delivery to offer intrapartum antibiotic prophylaxis only for GBS positive women.The goal of the present study is to report our experience and results from the first half year of GBS testing. Study design: This is a retrospective study. Rectovaginal swabs from 321 women presenting in the labor ward with pre-labor rupture of membranes for >14 h/rupture of membranes during delivery for >14 h, or labor between gestational weeks 35 0/7 and 36 6/7 from February 7, 2017 to August 6, 2017, were tested.We performed a molecular GBS test (Xpert GBS®, Cepheid Ltd., Sunnyvale, USA).Data from patient files including mode of delivery, use of antibiotics, infection of mother and child are presented in more detail.Data on the PCR results from the first year of testing were also collected. Results: In the first half-year of testing a positive GBS test result was found in 58 (18.1%) and a negative test result in 263 women (81.9%). No invalid test result was achieved.The indication for performing PCR testing was PROM > 14 h or rupture of membranes during labor for >14 h in 266 women (82.9%) and labor in gestational weeks 35 0/7-36 6/7 in 44 women (13.7%). In the remaining 11 women, the PCR test was performed for other reasons.Of the 321 women tested 126 (39%) received antibiotics during labor.Ten women (3.4%) were treated after delivery on suspicion of infection. 25 newborns (7.8%) were treated with antibiotics. In 11 cases, the treatment was stopped after 2-4 days as there were no signs of infection. Conclusions: The introduction of the intrapartum GBS test in selected groups of women who gave birth in our department has been well accepted by the women, the midwifes and doctors. The result of the test is available within two hours, and as we only offer intrapartum antibiotic prophylaxis to GBS-positive women, we have reduced the use of antibiotics to approximately 40% in the groups tested, without an increase of infection in mother or child. Keywords: Early-onset GBS disease, Group B streptococcus, Intrapartum antibiotic prophylaxis, PCR-assay for GBS, PROM, Intrapartum PCR-assay for detection of GBS